Resveratrol Supplementation Modulates Endothelial Dysfunction in Alzheimer’s Disease (AD): In Vitro Effects on Human Aortic Endothelial Cells Exposed to AD Plasma - Schiavoni, Valentina; Alia, Sonila; Pompei, Veronica; Fiori, Chiara; Luzzi, Simona; Vignini, Arianna; Salvolini, Eleonora; Silvestrini, Mauro; Emanuelli, Monica (Current Neuropharmacology, 2025)
<span class=
Keywords: membrane fluidity